Index Penulis Jurnal Teknologi Industri Pertanian - Index Penulis JTIP (Jurnal Teknologi Industri Pertanian, 2016)
INDEKS PENULISVOLUME 26Achmadi, F. 189Ahmad, U. 162Akmal, S. 171Anggarani, R.R. 276Arkeman, Y. 31, 153, 207Astuti, R. 189Boer, R. 153Cepeda, G.N. 41Cherie, D. 162Damsir 125Diah, F.P.D. 199Djatna, T. 309Elvina, W. 104Eris, F.R. 266Fauzi, A.M. 255Ferdian, M.A. 60Gaspers, V. 207Haditjaroko, L. 134, 300, 320Hambali, E. 60, 104, 153Haryadi, P. 31Herastuti, S.R. 23Herlambang, A. 125Hermawan, A. 246Hermawan, D. 68, 216Herodian, S. 162Hidayati, J. 255Husin, H. 293Kartawiria, I.S. 143Kartika, I.A. 68, 216Legowo, E.H. 143Lina, A.D. 68Lisangan.M.M. 41Lubis, A.S. 77Maarif, M.S. 87, 246Machfud 49Mahlinda 293Maknunah, L.U. 189Mandang, T. 162Marbun, B.T.H. 332Marimin 9, 199, 309Mawardi, M.I. 153Meryandini, A. 111, 283Noor, E. 143Nugroho, L.P.E. 236Nurhayati 309Pari, G. 77Permadi, P. 266Permana, A.I.S. 9Permana, I.G. 309Prasetya, H. 153Pratama, M. 320Purbowati, I.S.M 23Purwanti, N. 342Purwoko 134Raharja, S. 31, 87Rahayuningsih, M. 60, 276Riza, M. 293Romli, M. 77, 125, 134Saharjo.B.H. 207Sampebatu, L.S. 207Santoso, I. 216Saparudin 342Sari, S.P. 236Sarono 171Sartika, E. 41Setiawan, F. 216Silamba, I. 41Subyakto 177Sugiarto 1Sugiharto 255Sukardi 87, 177, 255Sunarti, T.C. 1, 111, 283Supardan, M.D. 293Suparno, O. 49, 68Suprayitno, G. 9Suprihatin 125Suryani, A. 1, 177, 255Suseno, D. 111Sutrisno 1Syamani, F.A. 177Syamsu, K. 23, 143Syarief, R. 199Tambunan, A.H. 236Tarwa 49Ulfah, M. 87Wahyuni, S. 332Warsiki, E. 23, 276, 320Wisudawaty, P. 300Wulandari D. 342Yani, M. 77, 104, 125Yeni 283Yuliasih, I. 1, 300Yusriana 31Zulfahmi 171